Physiological winners and losers in an ocean warming hotspot: a Case study on argyrosomus off the Namibian coast, with implications for their future management - Pringle, Brett Andrew (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Anthropogenic-induced climate change is having a profound impact on aquatic ecosystems, and the resilience of fish populations will be determined by how they respond to these impacts. Changes in ocean water temperature is regarded as the most pervasive change, and affects the biological, physiological and distribution response of species, particularly ectotherms. The increasingly variable biological responses to a changing environment suggest that some species and populations will likely prove to be more tolerant than others. The northern Namibian coast is an ocean warming hotspot, with temperatures rising at approximately ten times the global average. These rapid changes are predicted to have a considerable impact on the marine fauna. One recently documented change in distribution is a southern extension of the sciaenid, Argyrosomus coronus, from southern Angola into northern Namibian waters, where it now overlaps with the closely related Namibian species, Argyrosomus inodorus. Understanding how these species perform at current and future temperatures and where they overlap is vital to optimise any adaptive management for the Argyrosomus species, which forms a large component of Namibia's coastal commercial, recreational and subsistence fisheries. The aim of this study was to quantify the aerobic scope of both species (A. coronus and A. inodorus), to determine which Argyrosomus species will be a winner at the current and future climate predictions and to provide recommendations for the sustainable management of the Namibian Argyrosomus fishery. Intermittent flow-through respirometry was used to quantify standard and maximum metabolic rates for both species across a range of temperatures. Results showed that metabolic rates scaled positively with temperature. It appears that the aerobic scope of A. inodorus was notably higher at most temperatures (12, 15, 18 and 21ËšC), while that of A. coronus was only higher at the warmest test temperature of 24ËšC. This corresponded with the contemporary biogeographic patterns of each species. Based on these findings, it is likely that the warming ocean conditions in northern Namibia and the cold Lüdertiz upwelling cell south of Walvis Bay will constrain these fish to central Namibia. While both species demonstrated signs of resilience to high temperatures, it is likely that the warming conditions will increasingly favour A. coronus, and that the leading edge of their distribution will shift southward in Namibia. The distribution of A. inodorus is likely to contract, as the energy budget of those on the northern trailing edge will be compromised. To promote the sustainable utilisation of the complex Argyrosomus fishery, adaptive management strategies need to be implemented. This will only be possible with a comprehensive monitoring program, including the collection of genetic data to inform the changing proportions of the two species. To maintain the A. coronus population, the current regulations need to be re-assessed, and harvest slots should be introduced to protect juvenile A. coronus and the fecund large females of both species.
Keywords: Argyrosomus Benguela Current; Ocean temperature Benguela Current; Sciaenidae Benguela Current; Argyrosomus Physiology Benguela Current; Argyrosomus Geographical distribution Climatic factors Benguela Current; Argyrosomus Effect of temperature on Benguela Current; Sciaenidae fisheries-- Namibia; Fishery management-- Namibia; Sustainable fisheries-- Namibia